2023
DOI: 10.1007/s00432-023-04650-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the inflammatory tumor microenvironment of esophageal adenocarcinoma: mast cells and natural killer cells are favorable prognostic factors and associated with less extensive disease

Abstract: Purpose Esophageal adenocarcinoma (EAC) remains a challenging and lethal cancer entity. A promising target for new therapeutic approaches, as demonstrated by the success of immune checkpoint inhibitors, are tumor-associated immune cells and the tumor microenvironment (TME). However, the understanding of the TME in esophageal cancer remains limited and requires further investigation. Methods Over 900 EAC samples were included, including patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In a few retrospective studies, high-grade tumor budding in early EACs has been described as an independent risk factor for LNM and poor prognosis [ 38 , 43 45 ]. Moreover, some studies have also reported a significant correlation of certain immune cell types with LNM and survival rates [ 46 ▪ , 47 ▪ , 48 ]. Although our understanding for EAC is still limited, these results might point towards a possibly valuable direction for further research.…”
Section: Towards Personalized Managementmentioning
confidence: 99%
“…In a few retrospective studies, high-grade tumor budding in early EACs has been described as an independent risk factor for LNM and poor prognosis [ 38 , 43 45 ]. Moreover, some studies have also reported a significant correlation of certain immune cell types with LNM and survival rates [ 46 ▪ , 47 ▪ , 48 ]. Although our understanding for EAC is still limited, these results might point towards a possibly valuable direction for further research.…”
Section: Towards Personalized Managementmentioning
confidence: 99%
“…Lymph node and distant site metastases worsen the prognosis. Lower levels of immune cells, specifically CD8+ T cells, have been associated with higher lymph node invasion ( 17 , 18 , 21 , 36 ). Macrophages tend to have an immunoregulatory phenotype in nodal-spread OAC ( 28 ).…”
Section: Oac Tmementioning
confidence: 99%
“…Several studies describing the TME in OAC associated clinical outcomes to the presence or absence of specific cell populations. It is widely accepted that a higher level of total immune cells, or total tumour-infiltrating lymphocytes, is linked to longer overall survival (OS) independently from the chosen therapeutic approach (17)(18)(19)(20)(21)(22). Derks et al reported OAC had a lower T cell density compared to gastric tumours (23).…”
Section: Tme Composition and Clinical Significancementioning
confidence: 99%
“… 5 Furthermore, high levels of eosinophils and mast cells each correlate with favorable outcomes in esophageal cancer patients. 7 , 8 , 9 , 10 Notably, however, the direct role of eosinophils in ESCC has remained elusive.…”
mentioning
confidence: 99%
“…Of course, although the current study shows that eosinophils promote apoptosis in ESCC cells in vitro, it will be imperative to determine whether eosinophils are capable of inducing ESCC regression in vivo. Because eosinophilia also has been detected in subsets of patients with Barrett’s esophagus or esophageal adenocarcinoma, 10 , 12 it will be of further interest to determine if eosinophils exert antitumor activity in this context as well. The technical feasibility of harnessing the antitumor activity of eosinophils in esophageal cancer lesions also represents an important consideration.…”
mentioning
confidence: 99%